A sulfide solid electrolyte material and a preparation method and application thereof
Patent Information
- Application Number
- CN202611229880.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
若包覆层离子绝缘性过强,可能增加颗粒间离子迁移阻抗,影响电池性能
本发明利用钼源在硫化物固态电解质颗粒表面与硫物种形成Mo-S键的作用,降低硫化物固态电解质面硫离子的反应活性,增强表面P-S结构单元和硫化物骨架对水分子的抵抗能力,从而抑制水解反应,减少H2S释放,提高空气暴露后的结构稳定性、离子电导率保持率和电化学性能。本发明是对已合成硫化物固态电解质粉体的表面后处理改性,不需要大量Mo和其他元素进入电解质主体晶格,在不显著破坏硫化物固态电解质主体晶相、不明显牺牲离子电导率、简化制备流程的前提下,提升硫化物固态电解质的空气稳定性。
Smart Images

Figure CN123018082A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a sulfide solid electrolyte material, its preparation method, and its application. Background Technology
[0002] With the rapid development of new energy vehicles, energy storage power stations, and portable electronic devices, traditional liquid organic electrolytes suffer from problems such as flammability and insufficient thermal stability, making it difficult to meet the demands of next-generation high-safety, high-energy-density batteries. All-solid-state lithium batteries use non-flammable solid electrolytes to replace traditional liquid electrolytes, offering higher safety and the potential to improve battery energy density when paired with lithium metal anodes. Among various solid electrolyte systems, sulfide-germanium sulfide solid electrolytes exhibit high room-temperature ionic conductivity and excellent processability, showing promising commercialization prospects. However, the PS and Li-S bonds in sulfide solid electrolytes are susceptible to attack by water molecules, leading to hydrolysis and the generation of toxic and corrosive H2S gas, which also damages the electrolyte crystal structure, resulting in a decrease in ionic conductivity and overall electrochemical performance. Therefore, improving the stability of sulfide solid electrolytes in air is a key issue that must be addressed for the large-scale fabrication and application of sulfide all-solid-state batteries.
[0003] Currently, methods for modifying the air stability of sulfide solid electrolytes include using Li3N as a doping source and N... 3- Partially replaces S 2- Li was prepared by ball milling and solid-state sintering. 5.55 PS 4.45 N 0.05 Cl 1.5 , original Li 5.55 PS 4.45 N 0.05 Cl 1.5 The ionic conductivity was 10.2 mS / cm, and 7.2 mS / cm for the N-doped sample. At the dew point... After exposure to air at 50℃ for 5 hours, the ionic conductivity of the N-doped sample remained at 71%, while that of the original sample was only 40.2%. The optimal sample obtained by ball milling BaTiO3 nanoparticles to coat the sulfide electrolyte was LPSC1.5@10BTO. After exposure to air at 30%RH and 25℃ for 2 hours, the ionic conductivity of the original LPSC1.5 decreased from 11.37 mS / cm to 2.06 mS / cm; that of LPSC1.5@10BTO decreased from 9.59 mS / cm to 3.49 mS / cm.
[0004] In existing technologies, elemental doping to improve the air stability of sulfide solid electrolytes typically requires high-temperature solid-phase reactions. This method involves high preparation temperatures, lengthy processes, and strict requirements on raw material ratios, doping amounts, and sintering temperatures. It also generally reduces the ionic conductivity of the solid electrolyte, thus having certain limitations. Coating methods primarily function by physically blocking moisture, requiring a high degree of continuity and integrity of the coating layer. If the coating layer is too thin or uneven, water molecules can still directly contact the electrolyte in defect areas and cause hydrolysis. If the coating layer has excessively strong ionic insulation, it may increase the interparticle ion migration resistance, affecting battery performance. Summary of the Invention
[0005] Based on this, the purpose of this invention is to provide a sulfide solid electrolyte material, its preparation method, and its application. By utilizing the effect of molybdenum source to form Mo-S bonds with sulfur species on the surface of sulfide solid electrolyte particles, the reactivity of sulfur ions on the surface of sulfide solid electrolyte is reduced, and the resistance of the surface PS structural units and sulfide skeleton to water molecules is enhanced, thereby inhibiting hydrolysis reaction, reducing H2S release, and improving structural stability, ionic conductivity retention, and electrochemical performance after air exposure.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: The present invention provides a sulfide solid electrolyte material, which includes a core and a shell covering the core. The core includes a sulfide solid electrolyte, and the shell is a molybdenum-based compound, with Mo-S bonds formed at the interface between the core and the shell.
[0007] P in LiPSX 5+ Slightly hard acid, S 2- It is a soft base, and the PS bond is a relatively unstable hard acid-soft base combination; the O in the water molecule 2- As a hard alkali, it is more likely to react with P. 5+ The combination forms a PO bond, generating a stable hard acid-hard base combination, which leads to the breaking of the PS bond, hydrolysis releasing H2S, and a decrease in ionic conductivity. This invention utilizes the ability of molybdenum species to combine with S at the sulfide interface. 2- The formation of Mo-S bonds with strong covalent characteristics reduces the reactivity of surface sulfur ions, inhibits the attack of water molecules on PS bonds, stabilizes the surface structure of LiPSX, and improves the air stability of LiPSX.
[0008] As a further improvement of the above-mentioned solution of the present invention, the coating amount of the shell layer is 2% to 4% of the mass of the sulfide solid electrolyte material, and the thickness is 50 to 100 nm; the molybdenum-based compound is molybdenum trioxide, molybdenum dioxide, thiomolybdate, or a molybdenum-containing carbonyl complex; the molybdenum-containing carbonyl complex is mesitylenetricarbonylmolybdenum or pseudotrimethyllenetricarbonylmolybdenum.
[0009] As a further improvement to the above-described scheme of the present invention, the chemical formula of the sulfide solid electrolyte is LiPSX, wherein X is at least one of Cl, Br, Si, and O.
[0010] The present invention also provides a method for preparing the sulfide solid electrolyte material as described above, which includes the following steps: ball milling and mixing sulfide solid electrolyte powder and molybdenum source powder to obtain the sulfide solid electrolyte material.
[0011] As a further improvement to the above-mentioned scheme of the present invention, the molybdenum source is molybdenum trioxide, molybdenum dioxide, or a molybdenum-containing carbonyl complex; in the sulfide solid electrolyte material, the mass percentage of the molybdenum source is 1% to 5%; the ball milling is performed at a rotation speed of 100 to 250 r / min for 1 to 5 hours.
[0012] As a further improvement to the above-mentioned scheme of the present invention, the molybdenum source is molybdenum trioxide or molybdenum dioxide; after the ball milling is completed, a heat treatment step is also included: under inert conditions, the temperature is raised to 100-150°C at a heating rate of 1-10°C / min and held for 1-5 hours.
[0013] The present invention also provides a method for preparing the sulfide solid electrolyte material as described above, which includes the following steps: under an inert atmosphere, molybdenum source powder is weighed and dissolved in a solvent, and ultrasonically dispersed to obtain a dispersion; sulfide solid electrolyte powder is added to the dispersion, stirred, filtered, dried, and heat-treated to obtain the sulfide solid electrolyte material.
[0014] As a further improvement to the above-mentioned solution of the present invention, the molybdenum source is thiomolybdate, and the mass ratio of the molybdenum source powder to the sulfide solid electrolyte powder is 20~70mg:1g; And / or, the heat treatment is performed by heating to 100-150°C at a heating rate of 1-10°C / min and holding for 1-5 hours in an inert atmosphere.
[0015] As a further improvement to the above-described scheme of the present invention, the molybdenum source is a molybdenum-containing carbonyl complex, and the mass ratio of the molybdenum source powder to the sulfide solid electrolyte powder is 20~70mg:1g; the molybdenum-containing carbonyl complex is mesitylenetricarbonylmolybdenum or metasitylenetricarbonylmolybdenum. The heat treatment involves uniformly spreading the dried powder in a crucible, placing the crucible downstream of a quartz tube, and spreading sulfur powder upstream of the quartz tube. The temperature is then raised to 120-180°C at a rate of 1-10°C / min under an inert atmosphere and held for 1-5 hours. The purpose of spreading the sulfur powder is to provide a gaseous sulfur source, allowing the molybdenum-containing carbonyl complex on the surface to form a Mo-S bond-containing interfacial passivation layer during the low-temperature heat treatment. The shell layer will also contain Mo-S bonds.
[0016] The present invention also provides an application of the sulfide solid electrolyte material as described above in solid-state batteries.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention utilizes the effect of molybdenum source to form Mo-S bonds with sulfur species on the surface of sulfide solid electrolyte particles, reducing the reactivity of sulfur ions on the sulfide solid electrolyte surface, enhancing the resistance of the surface PS structural units and sulfide framework to water molecules, thereby inhibiting hydrolysis, reducing H2S release, and improving structural stability, ionic conductivity retention, and electrochemical performance after air exposure. This invention is a surface post-treatment modification of synthesized sulfide solid electrolyte powder, which does not require large amounts of Mo and other elements to enter the electrolyte bulk lattice. It improves the air stability of sulfide solid electrolytes without significantly damaging the bulk crystal phase, without significantly sacrificing ionic conductivity, and with a simplified preparation process.
[0018] This invention is not limited to forming a simple physical coating layer. Instead, it utilizes mechanical ball milling, mechanical ball milling followed by low-temperature heat treatment, in-situ conversion of thiomolybdate solution, and surface sulfidation of organic molybdenum compounds to induce an interfacial reaction between molybdenum species and sulfur on the electrolyte surface, forming Mo-S bonds or an interfacial passivation layer containing Mo-S bonds. Unlike traditional inert oxide coatings, the Mo-S bonded interfacial layer of this invention can stabilize the active sites on the sulfide solid electrolyte surface through chemical bonding, even when the thickness is thin or locally discontinuous, reducing the attack of water molecules on the sulfide surface. Furthermore, the Mo-S bonded interfacial layer does not require an excessively thick ionic insulating coating layer; therefore, surface bonding provides a more stable interface than simple physical coating. All of these methods are suitable as post-treatment modification methods for sulfide solid electrolytes, showing promising prospects for large-scale application. Attached Figure Description
[0019] Figure 1 The XRD patterns of the sulfide solid electrolytes prepared in Examples 1-3 and Comparative Example 1 are shown below. Figure 2 XPS spectra of the sulfide solid electrolytes prepared in Example 2 and Comparative Example 1; Figure 3 SEM image of the sulfide solid electrolyte prepared in Example 2; Figure 4 The graph shows the changes in ionic conductivity of the sulfide solid electrolytes prepared in Example 2 and Comparative Example 1 before and after exposure. Figure 5 The graph shows the rate performance of all-solid-state batteries assembled before and after exposure of the sulfide solid electrolytes prepared in Example 2 and Comparative Example 1. Figure 6The graph shows the cycle performance of all-solid-state batteries assembled after exposure of the sulfide solid electrolytes prepared in Example 2 and Comparative Example 1. Detailed Implementation
[0020] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0022] Example 1 This embodiment proposes a sulfide solid electrolyte material, the preparation method of which is as follows: Under inert atmosphere, small particles of Li6PS5Cl solid electrolyte powder with a particle size of 1~5μm and nano MoO3 powder were added to a ball mill jar at a mass ratio of 98:2 and ball milled at 100r / min for 1h to uniformly coat the surface of LPSC particles with nano MoO3. After ball milling, the powder was collected in an inert atmosphere to obtain sulfide solid electrolyte material, denoted as 2%-M-LPSC.
[0023] Example 2 This embodiment proposes a sulfide solid electrolyte material, the preparation method of which is as follows: Under inert atmosphere, small particles of Li6PS5Cl solid electrolyte powder with a particle size of 1~5μm and nano MoO3 powder were added to a ball mill jar at a mass ratio of 97:3 and ball milled at a speed of 100r / min for 1h to uniformly coat the surface of LPSC particles with nano MoO3. After ball milling, the powder was collected in an inert atmosphere to obtain sulfide solid electrolyte material, denoted as 3%-M-LPSC.
[0024] Example 3 This embodiment proposes a sulfide solid electrolyte material, the preparation method of which is as follows: Under inert atmosphere, small particles of Li6PS5Cl solid electrolyte powder with a particle size of 1~5μm and nano MoO3 powder were added to a ball mill jar at a mass ratio of 96:4 and ball milled at a speed of 100r / min for 1h to uniformly coat the surface of LPSC particles with nano MoO3. After ball milling, the powder was collected in an inert atmosphere to obtain sulfide solid electrolyte material, denoted as 4%-M-LPSC.
[0025] Example 4 This embodiment proposes a sulfide solid electrolyte material, the preparation method of which is as follows: Under inert atmosphere, large-particle Li6PS5Cl solid electrolyte powder with a particle size of 20μm and nano MoO3 powder were added to a ball mill jar at a mass ratio of 97:3 and ball milled at a speed of 250r / min for 1h to uniformly coat the surface of LPSC particles with nano MoO3. After ball milling, the powder was collected in an inert atmosphere to obtain sulfide solid electrolyte material, denoted as 3%-M-LPSC-D.
[0026] Example 5 This embodiment proposes a sulfide solid electrolyte material, the preparation method of which is as follows: Under inert atmosphere, small Li6PS5Cl solid electrolyte powder with a particle size of 1~5μm and nano MoO3 powder were added to a ball mill jar at a mass ratio of 97:3 and ball milled at 100r / min for 1h to uniformly coat the surface of LPSC particles with nano MoO3. The ball-milled powder was then placed in a muffle furnace and heated to 120℃ at a heating rate of 5℃ / min under inert atmosphere and held for 1h to obtain sulfide solid electrolyte material, denoted as 3%-M-LPSC-H.
[0027] Example 6 This embodiment proposes a sulfide solid electrolyte material, the preparation method of which is as follows: Under an inert atmosphere, 40 mg of ammonium thiomolybdate (NH4)2MoS4 was dissolved in anhydrous xylene and ultrasonically dispersed for 10 min to obtain a thiomolybdate precursor dispersion. 1 g of Li6PS5Cl powder (particle size 1-5 μm) was added to the thiomolybdate precursor dispersion and magnetically stirred for 1 h. After stirring, the resulting suspension was filtered, and the solid powder was collected and dried to powder form in a vacuum oven at 80 °C. The resulting powder was placed in a muffle furnace and heated to 150 °C at a rate of 5 °C / min under an inert atmosphere and held for 2 h to obtain a sulfide solid electrolyte material, denoted as LPSC@(NH4)2MoS4.
[0028] Example 7 This embodiment proposes a sulfide solid electrolyte material, the preparation method of which is as follows: Under an inert atmosphere, 40 mg of mesitylenetricarbonylmolybdenum was dissolved in anhydrous xylene and ultrasonically dispersed for 6 min to obtain a molybdenum-containing precursor solution. 1 g of Li6PS5Cl powder (particle size 1-5 μm) was added to this molybdenum-containing precursor solution and magnetically stirred for 1 h. After stirring, the resulting suspension was filtered, and the solid powder was collected and dried to powder form in a vacuum oven at 80 °C. The obtained powder was evenly spread in an alumina crucible, which was placed downstream of a quartz tube. 15 mg of sulfur powder was placed upstream of the quartz tube. The crucible was heated to 160 °C in a tube furnace under an argon atmosphere at a heating rate of 5 °C / min and held for 2 h to obtain a sulfide solid electrolyte material, denoted as LPSC@mesitylenetricarbonylmolybdenum.
[0029] Example 8 This embodiment proposes a sulfide solid electrolyte material, the preparation method of which is as follows: Under inert atmosphere, Li6PS5Cl solid electrolyte powder (particle size 1~5μm) and molybdenum hexacarbonyl powder were added to a ball mill jar at a mass ratio of 97:3 and ball milled at 100 r / min for 1 h. After ball milling, the powder was collected in an inert atmosphere to obtain the sulfide solid electrolyte material, denoted as LPSC@molybdenum hexacarbonyl.
[0030] Comparative Example 1 This comparative example presents a sulfide solid electrolyte material, the preparation method of which is as follows: Under inert atmosphere, small Li6PS5Cl solid electrolyte powder with a particle size of 1~5μm was added to a ball mill jar and ball milled at 100r / min for 1h. After ball milling, the powder was collected in an inert atmosphere to obtain sulfide solid electrolyte material, denoted as LPSC.
[0031] Comparative Example 2 This comparative example presents a sulfide solid electrolyte material, the preparation method of which is as follows: Under inert atmosphere, large-particle Li6PS5Cl solid electrolyte powder with a particle size of 20μm was added to a ball mill jar and ball milled at a speed of 250r / min for 1h. After ball milling, the powder was collected in an inert atmosphere to obtain sulfide solid electrolyte material, denoted as LPSC-D.
[0032] Comparative Example 3 This comparative example presents a sulfide solid electrolyte material, the preparation method of which is as follows: Under inert atmosphere, small particles of Li6PS5Cl solid electrolyte powder with a particle size of 1~5μm were added to a ball mill jar and ball milled at a speed of 100r / min for 1h. The ball-milled powder was then placed in a muffle furnace and heated to 120℃ at a heating rate of 5℃ / min under inert atmosphere and held for 1h to obtain a sulfide solid electrolyte material, denoted as LPSC-H.
[0033] Comparative Example 4 This comparative example presents a sulfide solid electrolyte material, the preparation method of which is as follows: Under an inert atmosphere, 1 g of Li6PS5Cl powder (particle size 1-5 μm) was added to anhydrous xylene solvent and magnetically stirred for 1 h. After stirring, the resulting suspension was filtered to collect the solid powder, which was then dried to powder form in a vacuum oven at 80 °C. The resulting powder was placed in a muffle furnace and heated to 150 °C at a heating rate of 5 °C / min under an inert atmosphere and held for 2 h to obtain a sulfide solid electrolyte material, denoted as LPSC@.
[0034] Test case (1) The sulfide solid electrolytes obtained in Examples 1-3 and Comparative Example 1 were characterized to obtain the following results: Figure 1 The XRD pattern shown Figure 2 The XPS graph shown Figure 3 The SEM image shown.
[0035] Figure 1 The XRD patterns are of the sulfide solid electrolytes obtained in Examples 1-3 and Comparative Example 1. Figure 1 The results show that the introduction of nano MoO3 in Examples 1-3 did not significantly disrupt the LPSC crystal structure.
[0036] Figure 2 XPS spectra of the sulfide solid electrolytes obtained in Example 2 and Comparative Example 1. Figure 2 The results show that MoO3 and LPSC can be combined by simple mechanical ball milling to obtain an LPSC solid electrolyte with Mo-S bonds forming at the core-shell interface.
[0037] Figure 3 This is an SEM image of the sulfide solid electrolyte prepared in Example 2. Figure 3 The results show that the nano-MoO3 particles are uniformly dispersed on the surface of LPSC particles, forming a relatively uniform physical protective layer while forming Mo-S bonds.
[0038] (2) The same mass of the sulfide solid electrolytes prepared in Examples 1-8 and Comparative Examples 1-4 were evenly spread on glass plates and exposed to air at a dew point of -50°C for 12 hours. The sulfide solid electrolytes of Examples 1-8 and Comparative Examples 1-4 after exposure were obtained.
[0039] The ionic conductivity of the sulfide solid electrolytes prepared in Examples 1-8 and Comparative Examples 1-4 before and after exposure was tested: Electrochemical impedance spectroscopy (EIS) was first performed using a Bio-Logic SP-200 electrochemical workstation (frequency range: 7 MHz~1 Hz). 120 mg of electrolyte powder was placed in a polytetrafluoroethylene (PTFE) mold and pressed into a dense electrolyte sheet with a diameter of 10 mm under a pressure of 400 MPa. The thickness D (cm) and area S (cm²) of the electrolyte sheet were measured. 2 The electrolyte sheet was connected to the stainless steel rods at both ends directly using stainless steel rods as blocking electrodes. The impedance R was obtained by testing under a constant pressure of 100 MPa. The ionic conductivity was then calculated using the formula: D / (S×R).
[0040] H2S release in 90 seconds: Weigh 1g of electrolyte powder and place it evenly in a box containing an H2S gas detector. Turn on the H2S gas detector, seal the box and start timing. Record the instrument value after 90 seconds.
[0041] The test results are shown in Table 1. Figure 4 As shown.
[0042] Table 1 Test Results
[0043] As shown in Table 1, the LPSCs with Mo-S bonds formed at the core-shell interface in Examples 1-8 of this invention exhibited higher ionic conductivity retention rates after 12 hours of exposure in air at a dew point of -50°C compared to the LPSCs without Mo-S bonds at the core-shell interface in Comparative Examples 1-4, and their H2S gas release was reduced. This indicates that the formation of Mo-S bonds at the interface of the sulfide solid electrolyte can improve the air stability of the sulfide solid electrolyte.
[0044] (2) The sulfide solid electrolytes prepared in Example 2 and Comparative Example 1 before and after exposure to a dew point of -50℃ were assembled into all-solid-state batteries: NCM811 material, sulfide solid electrolyte, and vapor-grown carbon fiber VGCF were mixed at a mass ratio of 8:2:0.2, placed in a stainless steel container, and ball-milled at 200 r / min for 1 h to obtain a composite cathode; lithium sheets and nano-silicon powder were mixed at a molar ratio of 1:3.2, and ball-milled at 550 r / min for 10 h in a stainless steel container to obtain Li 3.2 Si negative electrode; composite positive electrode, Li 3.2A Si anode was assembled into an all-solid-state battery. The resulting all-solid-state battery was subjected to cycle performance and rate performance tests, with current ranging from 0.1C to 2C. The test results are as follows: Figure 5 , Figure 6 As shown.
[0045] Figure 5 The graphs show the rate performance of all-solid-state batteries assembled with electrolytes before and after exposure in Example 2 and Comparative Example 1. The test results before exposure show that the addition of 3% MoO3 has almost no effect on the rate performance; however, the rate performance of 3%-M-LPSC after exposure is better than that of LPSC after exposure, indicating that MoO3 can improve the air stability of LPSC without affecting the electrochemical performance of the electrolyte.
[0046] Figure 6 The graph shows the cycle performance of the all-solid-state batteries assembled with electrolytes after exposure in Example 2 and Comparative Example 1. At 1C rate, the initial discharge capacity and cycle performance of the 3%-M-LPSC after exposure are better than those of the LPSC after exposure.
[0047] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0048] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A sulfide solid electrolyte material, characterized in that, It includes a core and a shell covering the core. The core includes a sulfide solid electrolyte, and the shell is a molybdenum-based compound, with Mo-S bonds formed at the interface between the core and the shell.
2. The sulfide solid electrolyte material according to claim 1, characterized in that, The coating amount of the shell is 1% to 5% of the mass of the sulfide solid electrolyte material, and the thickness is 50 to 100 nm; the molybdenum-based compound is molybdenum trioxide, molybdenum dioxide, thiomolybdate, or a molybdenum-containing carbonyl complex.
3. The sulfide solid electrolyte material according to claim 1, characterized in that, The chemical formula of the sulfide solid electrolyte is LiPSX, wherein X is at least one of Cl, Br, Si, and O.
4. A method for preparing a sulfide solid electrolyte material as described in any one of claims 1-3, characterized in that, It includes the following steps: The sulfide solid electrolyte powder and the molybdenum source powder were ball-milled and mixed to obtain the sulfide solid electrolyte material.
5. The method for preparing the sulfide solid electrolyte material according to claim 4, characterized in that, The molybdenum source is molybdenum trioxide, molybdenum dioxide, or a molybdenum-containing carbonyl complex; in the sulfide solid electrolyte material, the mass percentage of the molybdenum source is 1% to 5%; the ball milling is performed at a speed of 100 to 250 r / min for 1 to 5 hours.
6. The method for preparing the sulfide solid electrolyte material according to claim 4, characterized in that, The molybdenum source is molybdenum trioxide or molybdenum dioxide; after the ball milling is completed, a heat treatment step is also included: under inert conditions, the temperature is raised to 100-150℃ at a heating rate of 1-10℃ / min and held for 1-5 hours.
7. A method for preparing a sulfide solid electrolyte material as described in any one of claims 1-3, characterized in that, It includes the following steps: Under an inert atmosphere, molybdenum source powder was weighed and dissolved in a solvent, then ultrasonically dispersed to obtain a dispersion. Sulfide solid electrolyte powder was added to the dispersion, stirred, filtered, dried, and heat-treated to obtain the sulfide solid electrolyte material.
8. The method for preparing the sulfide solid electrolyte material according to claim 7, characterized in that, The molybdenum source is a thiomolybdate, and the mass ratio of the molybdenum source powder to the sulfide solid electrolyte powder is 20~70mg:1g; And / or, the heat treatment is performed by heating to 100-150°C at a heating rate of 1-10°C / min and holding for 1-5 hours in an inert atmosphere.
9. The method for preparing the sulfide solid electrolyte material according to claim 7, characterized in that, The molybdenum source is a molybdenum carbonyl complex, and the mass ratio of the molybdenum source powder to the sulfide solid electrolyte powder is 20~70mg:1g; The heat treatment involves evenly spreading the dried powder in a crucible, placing the crucible downstream of a quartz tube, spreading sulfur powder upstream of the quartz tube, and heating the crucible to 120-180°C at a heating rate of 1-10°C / min under an inert atmosphere and holding it at that temperature for 1-5 hours.
10. The application of a sulfide solid electrolyte material as described in any one of claims 1-3 in a solid-state battery.
